Control of two-degree-of-freedom vortex induced vibrations of a circular cylinder using synthetic Jets: Effect of synthetic jet orientation angle and phase difference. (1st December 2020) - Wang, Haibo; Ding, Lin; Zhang, Li; Zou, Qunfeng; Sharma, Rajnish N.
Abstract: Two-degree-of-freedom vortex induced vibrations (2DOF VIVs) of a circular cylinder controlled by synthetic jets in laminar flow are numerically investigated. The influence of synthetic jet orientation angle and phase difference on the oscillation characteristics, hydrodynamic forces and vortex shedding are discussed. The acting mechanisms of synthetic jets are also revealed. The numerical results show that the synthetic jet orientation angle is a key factor, which can determine whether the oscillation of the circular cylinder is suppressed or enhanced. 2DOF VIVs of the circular cylinder can be suppressed when synthetic jets are issued horizontally, but when controlled by synthetic jets issued vertically, they are enhanced. Under the control of synthetic jets issued in the normal direction, the suppression or enhancement of 2DOF VIVs are determined by the position angle. Furthermore, synthetic jets with different orientation angles can effectively control 2DOF VIVs of the circular cylinder in a wide range of reduced velocities. Compared with the cross-flow oscillation, the in-flow oscillation is more sensitive to the phase difference. The root-mean-square values of lift coefficients usually increase with the increase of phase difference. The vortex shedding in the wake is completely dominated by synthetic jets, and the vortices are elongated and symmetric when two-degree-of-freedom VIVs of the circular cylinder are effectively suppressed by synthetic jets ( β = 0°, α = 45°). Highlights: The synthetic jet orientation angle plays an important role on VIV control. Cross-flow oscillation frequencies may equal to synthetic jet excitation frequency. Lift coefficients are very sensitive to phase difference between synthetic jets. When β = 0°, synthetic jets delay boundary layer separation in two operating cycles.